2007
DOI: 10.1017/s0950268807008552
|View full text |Cite
|
Sign up to set email alerts
|

Limited impact of tuberculosis control in Hong Kong: attributable to high risks of reactivation disease

Abstract: SUMMARYOver 50% of the global burden of tuberculosis occurs in South East Asia and the Western Pacific. Since 1950, notification rates in high-income countries in these settings have declined slowly and have remained over ten-fold greater than those in Western populations. The reasons for the slow decline are poorly understood. Using an age-structured model describing the incidence of Mycobacterium tuberculosis infection and disease applied to notification data from Hong Kong, we illustrate that in Hong Kong, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 13 publications
3
60
0
Order By: Relevance
“…The value for m is consistent with human populations with life expectancy of 70 years, whereas f and t are consistent with the medical literature [12]. The rate of relapse (v) is fixed at the higher end of published estimates (v ¼ 0.01 yr 21 ) [13][14][15][16][17], with justification and sensitivity analysis provided in the electronic supplementary material. Parameters referring to the reinfection factor (s) and risk heterogeneity are estimated in order to adjust the equilibrium model solutions to the available data.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The value for m is consistent with human populations with life expectancy of 70 years, whereas f and t are consistent with the medical literature [12]. The rate of relapse (v) is fixed at the higher end of published estimates (v ¼ 0.01 yr 21 ) [13][14][15][16][17], with justification and sensitivity analysis provided in the electronic supplementary material. Parameters referring to the reinfection factor (s) and risk heterogeneity are estimated in order to adjust the equilibrium model solutions to the available data.…”
Section: Methodssupporting
confidence: 78%
“…This may be due to higher prevalence of co-infection with HIV in those settings or simply reflect regional differences in nutrition, smoking patterns, environmental conditions, population structure or the natural history of TB [16,17,35,36]. Despite these acknowledged differences, we have opted for constancy across regions in model parameters, with the exception of the force of infection, because our objective is to make inferences about the global epidemiology of TB.…”
Section: Discussionmentioning
confidence: 99%
“…19,74 The relative influence of other TB risk factors on reactivation and reinfection is even less well-characterized. Age is of particular importance; if reactivation rates increase with age, 7577 tuberculosis may become harder to eliminate as populations become older. Such considerations are also relevant when projecting the impact of interventions (e.g., IPT for HIV/TB-coinfected patients 78 ) that differentially affect reactivation and recent infection.…”
Section: The Tb Modeler’s “Wish List”mentioning
confidence: 99%
“…(1997) and Vynnycky et al (2008) 0.08/yr Selwyn et al (1989Selwyn et al ( , 1992 and Badri et al (2002) Lawn et al (2006) Parameters k y and g y were updated to stabilize the annual risk of infection in accordance with a study which found the risk to have been constant over the last decade in this community (Middelkoop et al, 2008). Recent estimates for endogenous reactivation (Vynnycky et al, 2008) suggest that it is closer to a y ¼ 0.002 than to the value of a¼ 0.0003 used in Bacaer et al (2008, results to those that would be obtained from a large number of exact stochastic realizations.…”
Section: Simulation Resultsmentioning
confidence: 99%